Reflective Practice: Effective Strategies for Combatting Challenges with Grading Policies - Amanda J. Smith (Journal of Scholarly Engagement)
This reflective practice aims to identify and evaluate possible strategies to overcome certain limitations of the world language departmental grading policies in the high school where I teach. As a French teacher at a large public suburban high school in the northeastern United States, I sought to examine the problem of not knowing which strategies were most effective in overcoming my challenges with specific grading policies. John Dewey’s theories of reflection and experience provided the theoretical lens with which I explored the problem. I identified strategies associated with four categories of challenges and engaged in reflective evaluation and decision-making based on my experiences and the expertise of other scholars. The reflective process was stimulating, complex, and contemplative. Engaging in reflective practice was critical to evaluating the merits of my practices and identifying effective strategies to overcome certain limitations. I hope other educators, administrators, and policymakers can benefit from this reflection when considering best practices for grading students.